SAT0412 Biological Therapy in Psoriatic Arthritis (PSA): Differences between Switchers and Non-Switchers. (15th July 2016) - Ramos Pinheiro, R.; Brasileiro, A.; Brito, A.; Barreto, P.; Pinheiro, S.
Abstract : Background: Switching biological therapies is becoming increasingly common in routine management of PsA patients. However, evidence in this topic is still scarce. Predictive markers for an optimal approach to the sequential prescription of biologics are lacking. Objectives: In a population of PsA patients, we aimed to determine differences in baseline clinical and laboratory features between switchers and non-switchers. Methods: We conducted a retrospective analysis of the PsA patients followed at our outpatient clinic in the last 24 months. Demographic, clinical and laboratory data were collected. Severity of skin manifestations and peripheral arthritis at PsA onset were recorded using PASI and DAS28 score. Patients who changed biological therapies due to therapeutic failure (primary or secondary) or toxicity were defined as switchers. For comparison of clinical and laboratory features we used chi-square test for categorical variables and Mann-Whitney or T-Student test for continuous variables. Results: 58 PsA patients were included, 60.3% were women; the mean age at PsA and psoriasis (PsO) onset was 46.4 (±15) and 34.8 (±15) years, respectively. At PsA onset, 24.1% of patients had a PASI score>10 and a mean DAS of 3.76 (±1.0). Laboratory features, arthritis and extra-articular manifestations were assessed (Image). 94.8% of patients were prescribed with non-biologic DMARD therapy and 55.2% with biological therapy, after failing to respond to a classic DMARD treatment alone. Median time from diagnosis until biological therapy prescription was 25.9 (±56, 5) months. Out of 32 patients prescribed with biologics, 15 (46.9%) switched to another biologic agent, mainly due to secondary failure (63.6%), primary failure (18.2%) and adverse events (13.6%). 15.65% and 3.1% of patients required 2 or 3 switches. Etarnacept was the first line agent prescribed in the majority (78.8%) of patients. Adalimumab (73.3%) and ustekinumab (50.0%) were the most used agents as second and third line biological therapies, respectively. Switchers were significantly younger at psoriasis onset (25.6 (±13.8) vs 37.4 (±13.3) years, p=0.020) and also at PsA onset (33.3 (±9.6) vs 50.0 (±13.1) years, p<0.0001). They had higher PASI (p=0.011) levels comparing to non-switchers. Uveitis and axial involvement were significantly more common in switchers (p=0.047 and p=0.034, respectively). All patients starting biological therapy on the first 12 months after disease onset switched to another biological agent. Conclusions: Age at PsO and PsA onset is a well-established clinical factor with significant impact in disease severity and in skin and arthritis manifestations. Our work suggests that it might also play a role in first biological treatment failure determining a need to switch. Higher PASI score at PsA onset, axial involvement and uveitis also seem to be associated with more likelihood of switching. Our results should be considered exploratory. Larger studies are required to determine the role of these clinical features in predicting biological treatment switching. Disclosure of Interest: None declared